A covered stent system and a method of making the same

CN122973187APending Publication Date: 2026-10-27BIOTYX MEDICAL (SHENZHEN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610993632.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-12-31
Filing Date
2022-12-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

另发明专利申请CN113151980A中公开了一种静电纺丝覆膜支架,该覆膜支架是将静电纺丝制备好的支撑骨架内、外层覆膜经过360℃-400℃下烧结之后将支撑骨架内、外层覆膜熔融并通过粘合剂粘合在一起,该方法虽然可以大幅度提高覆膜与支撑骨架结合强度,但后续高温加热静电纺丝覆膜,会改变静电纺丝覆膜的孔隙率及覆膜结构,破坏了静电纺丝覆膜特有的优点,同时最终制备的PTFE管状覆膜支架的厚度为0.08-0.14mm,支撑骨架覆膜较厚,在体内的输送性能较差,增加血管损伤的风险

Benefits of technology

本发明所制备的覆膜支架,支撑骨架紧密的夹在内层覆膜和外层覆膜之中,在支撑骨架杆覆盖区域,内层覆膜层外壁侧与支撑骨架管腔内壁粘合,外层覆膜层内壁侧与支撑骨架外壁粘合。在支撑骨架网格中,内层覆膜外壁侧与外层覆膜内壁侧紧密粘合,并形成连续或不连续的粘结区域,增强了内层覆膜与外层覆膜之间的结合强度。与此同时,为了增强内、外覆膜层之间的力学性能,静电纺丝纤维层之间也有部分区域相互接触的纺丝被溶剂再次溶解、再次凝固粘结在一起,增强纺丝纤维层之间结合力及覆膜力学性能,使得静电纺丝层不容易分层。使用该方法制备的覆膜支架,纺丝与支撑骨架接合无需后续高温加热熔融粘结,也无需使用粘合剂粘结,覆膜保留了静电纺丝纤维丝径细、纺丝覆膜薄、孔隙率易于调节,覆膜具有较高的比表面积、较高孔隙率和良好的弹性,覆膜层结构易于模仿细胞外基质的组成和结构,有利于内皮细胞化和控制新生内膜增生,减少血栓形成,提升覆膜支架远期效果等技术优点。同时还具有以下优点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122973187A_ABST
    Figure CN122973187A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of medical devices, and particularly relates to a covered stent and a preparation method thereof. The covered stent provided by the application comprises an inner layer covering film, an outer layer covering film, and a supporting framework located between the inner layer covering film and the outer layer covering film, and the inner layer covering film and the outer layer covering film are bonded to each other in the area of the supporting framework grid. The covered stent provided by the application does not introduce additional adhesive, and does not need subsequent heating and melting to bond the inner layer covering film and the outer layer covering film of the supporting framework, and has the advantages of thin covering film, small compression diameter, high bonding strength of the inner layer covering film and the outer layer covering film, good mechanical properties of the covering film and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical device technology, specifically relating to a covered stent and its preparation method. Background Technology

[0002] A covered stent is an implantable medical device that covers a supporting framework with a choke membrane, enabling it to simultaneously open the lumen and seal any ruptures. Depending on the site of application, the diameter of covered stents varies from a few millimeters to tens of millimeters. Clinically, covered stents are mainly used to treat aneurysms, pseudoaneurysms, ruptured blood vessels, stenosis, occlusion, and other arteriovenous malformations caused by various reasons. Small-diameter covered stents are also frequently used in emergency situations involving coronary artery perforation during PCI (Percutaneous Coronary Intervention).

[0003] Currently, the main methods for stent coating include woven fabric suture coating, adhesive bonding coating, heat sintering bonding coating, support skeleton impregnation coating, and electrospinning coating. Among these, electrospinning coating is a mature and simple coating process widely used in the preparation of various coated stents. Coatings prepared by electrospinning have advantages such as large specific surface area, high porosity, and easily controllable membrane thickness. Because the surface of the coating prepared by electrospinning easily mimics the composition and structural design of the extracellular matrix, it facilitates endothelialization and controls neointimal proliferation, reducing stent thrombosis and resulting in a good prognosis. Therefore, this method is currently the most commonly used for preparing coated stents in the market. However, because the electrospinning coating method requires a sufficient distance between the polymer solution nozzle and the spinning receiving support skeleton during spinning, the inner diameter of a support skeleton with a small diameter is insufficient to generate the distance needed for electrospinning. This increases the technical difficulty of electrospinning the inner layer of the support skeleton from its inner wall. Consequently, when electrospinning a small-diameter support skeleton, it is impossible to simultaneously electrospin from both the inner and outer walls of the support skeleton. Usually, only a single layer of coating can be applied to the outer wall of the support skeleton. Alternatively, the inner layer of coating of the support skeleton needs to be electrospinned on a mold rod beforehand, and then the support skeleton is installed outside the inner layer of coating before electrospinning the outer layer of coating. This can also achieve the purpose of coating both the inner and outer walls of the support skeleton. However, simply performing the inner and outer wall coating of the support skeleton in two steps will result in the inner and outer layers of coating not adhering together, and the adhesion between the coating and the support skeleton will be low, limiting the application of this method.

[0004] Several studies have been published on improving the bonding strength between the inner and outer membranes of coated scaffolds. For example, patent CN108136078B discloses a double-layer electrospun coated scaffold, in which the inner and outer membranes of the supporting framework are bonded together using an adhesive, thereby improving the bonding strength between the inner and outer membranes. However, using adhesives to bond the membranes increases the difficulty of the process, and the use of adhesives also increases the use of excess materials, thus increasing biological risks. Another invention patent application, CN113151980A, discloses an electrospun coated stent. This coated stent involves sintering the inner and outer layers of the electrospun support skeleton at 360℃-400℃, then melting the inner and outer layers of the support skeleton and bonding them together with an adhesive. Although this method can significantly improve the bonding strength between the coating and the support skeleton, the subsequent high-temperature heating of the electrospun coating will change the porosity and structure of the electrospun coating, destroying the unique advantages of electrospun coating. At the same time, the thickness of the final PTFE tubular coated stent is 0.08-0.14mm, and the support skeleton coating is relatively thick, resulting in poor delivery performance in the body and increasing the risk of vascular damage. Summary of the Invention

[0005] To overcome the defects and shortcomings of the existing technology, the present invention provides a membrane scaffold and its preparation method, which does not introduce additional adhesives, does not require subsequent high-temperature heating and melting bonding, and has the characteristics of thin membrane, small outer diameter of the gripping layer, high bonding strength of the membrane layer, and good mechanical properties of the membrane. In addition, the membrane scaffold provided by the present invention also has the advantages of fast endothelialization of the lumen, rapid ingrowth of tissue cells in the membrane layer, no inflammatory reaction of the membrane scaffold, no excessive proliferation of the new intima, and low lumen stenosis rate.

[0006] The present invention provides a film-coated scaffold, comprising an inner film, an outer film, and a support frame located between the inner and outer films. The inner and outer films are bonded together within a support frame mesh.

[0007] The "support frame" described in this invention is a tubular body with an arbitrary pattern design; further, the "support frame" described in this invention is a tubular body composed of independent wave coils or wave coils connected to connecting rods. That is, in some embodiments, the support frame described in this invention is a tubular body composed of multiple independent wave coils, while in other embodiments, the support frame is a tubular body formed by multiple wave coils and multiple connecting rods connected to each other.

[0008] In this invention, "support grid" refers to the area on the side surface of the cylinder enclosed by the support that is covered by material, that is, the pattern structure of the support; "in the support grid" and "support grid area" both refer to the gaps in the support, that is, the area on the side surface of the cylinder enclosed by the support that is not covered by material.

[0009] The "inner and outer coating layers bonding together within the supporting framework mesh" described in this invention refers to the bonding between the multiple layers of the inner and outer coating layers within the supporting framework mesh. This enhances the adhesion between the inner and outer coating layers, thereby increasing the peel strength between them. Simultaneously, the multiple layers of the inner and outer coating layers also bond to each other, creating adhesive regions along the thickness direction of the coating layers and enhancing their mechanical properties.

[0010] The film-coated support provided by this invention includes the total arc length of the gap between the inner and outer film layers on any cross-section along the circumferential direction of the supporting frame. L 空隙 The arc length L of the entire cross-section 圆周 0.1%-5%, L 空隙 With L 圆周 The ratio, i.e., the proportion of voids on any cross-section of the covered support in the circumferential direction, is the porosity A, which can be calculated in the following way: A= ×100% Formula I, It should be noted that the circumference and arc length mentioned in this invention refer to the circumference of the supporting frame and the arc length on the circumference. Furthermore, the arc length of the gap refers to the corresponding arc length projected onto the circumference of the support, while the arc length of the entire cross-section refers to the arc length of the circumference formed by connecting the midpoints of the support rods of the supporting frame on that cross-section.

[0011] The membrane-coated scaffold provided by the present invention has a porosity of 70-90% for both the inner and outer membrane layers, and further, a porosity of 70-85% or 75%-88% for both the inner and outer membrane layers.

[0012] The film-coated scaffold provided by the present invention has an outer film thickness greater than the inner film thickness; the outer film thickness is 1.1-5 times the inner film thickness.

[0013] The coated scaffold provided by this invention has an inner coating thickness of 10-100 μm; the total wall thickness of the inner and outer coatings in the supporting framework grid is 30-500 μm, that is, the total thickness of the inner and outer coatings in the supporting framework grid is 30-500 μm. The inner coating of the coated scaffold provided by this invention is embedded in the supporting framework grid to a depth of 10 μm-350 μm, including but not limited to 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 200 μm, 230 μm, 250 μm, 280 μm, 300 μm, 350 μm, and 500 μm. Furthermore, the inner coating is embedded in the support skeleton grid to a depth of 10μm-300μm, and even further, the inner coating is embedded in the support skeleton grid to a depth of 20μm-300μm, 30μm-300μm, 40μm-300μm, or 50μm-300μm.

[0014] The covered stent provided by the present invention has a clamping diameter of 0.9-6 mm when clamped onto the dilating balloon catheter, and more specifically 0.9-4.5 mm, 0.9-5.0 mm, or 1.0-5.5 mm.

[0015] The film-coated scaffold provided by this invention uses materials selected from at least one of cellulose, chitin, hyaluronic acid, collagen, gelatin, sodium alginate, polyurethane (PU), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (E-PTFE), polylactic acid (PAL), poly(l-lactic acid) (PLLA), poly(D-lactide) (PDLLA), polyglycolic acid (PGA), polycaprolactone (PCL), polyamide (PA), and polyethylene terephthalate (PET). In some embodiments, the materials used for the inner and outer coatings are one of the aforementioned materials, such as gelatin for the inner coating and sodium alginate for the outer coating. In other embodiments, the inner and outer coatings are prepared from at least two of the aforementioned materials, and can be blends and / or copolymers of at least two or more of the aforementioned materials. That is, they can be simple blends of at least two materials, simple copolymers of at least two materials, or blends and copolymers of at least two of the aforementioned materials. For example, the inner coating is a blend of gelatin and sodium alginate, while the outer coating is a copolymer of polytetrafluoroethylene and polyamide, or the outer coating portion is a copolymer of polytetrafluoroethylene and polyamide. The polymer is partly a blend of polytetrafluoroethylene and polyamide; in some embodiments, the material of the inner coating can be the same as that of the outer coating, such as both the inner and outer coatings being a blend of gelatin and sodium alginate; in some embodiments, the material of the inner coating can also be different from that of the outer coating, such as the inner coating being gelatin and the outer coating being a copolymer of sodium alginate and polyurethane; in other embodiments, the inner and outer coatings can each be multilayer films spun from different materials, such as the bottom layer of the inner coating being collagen or a copolymer of sodium alginate and polyurethane, and the outer layer of the inner coating being gelatin or a copolymer or blend of L-polylactic acid and polyamide, etc.

[0016] The supporting skeleton in the film-coated scaffold provided by the present invention can be spherically expanding or self-expanding; it can also be biodegradable or non-biodegradable.

[0017] The film-coated scaffold provided by the present invention has an inner film that completely covers the support skeleton, and an outer film that covers 10-100% of the area along the radial length of the support skeleton.

[0018] The membrane-covered stent provided by the present invention carries a drug or radiopaque material in its inner membrane, outer membrane, or between the inner and outer membranes. The drug includes anticoagulants and / or antiproliferative agents. The radiopaque material is selected from at least one of barium sulfate, niobium trioxide, titanium dioxide, zirconium oxide, iodine compounds, elemental iodine, gold, platinum, osmium, rhenium, tungsten, iridium, rhodium, and tantalum. Further, the anticoagulant is selected from one or more of heparin, hirudin, sodium citrate, EDTA, aspirin, warfarin, and rivaroxaban. The antiproliferative agent is selected from one or more of sirolimus, tacrolimus, pimecrolimus, paclitaxel, colchicine, dexamethasone, prednisone, and hydrocortisone.

[0019] The film-coated scaffold provided by this invention has a support frame wall thickness of 30-300μm and a radial support force of 90-180kpa.

[0020] It should be noted that "carrying" in this invention refers to dissolving or / melting the drug or developing material into the coating material and then spraying them together to form a coating; it can also refer to coating the inner coating and outer coating with the drug or developing material on the side of the supporting skeleton near the support frame after each coating layer is prepared.

[0021] The coated scaffold provided by this invention has a peel strength between the spun fiber layers in the inner or outer coated layer of 0.01-0.2 N / mm, that is, a peel strength between the multiple spun fibers of each inner and outer coated layer of 0.01-0.2 N / mm; and a peel strength between the inner and outer coated layers of 0.1-0.5 N / mm. The coated scaffold with the inner and outer coated layers bonded together by this invention exhibits a peel strength between the inner and outer coated layers that is greater than the peel strength between the spun fiber layers of each inner or outer coated layer. In other words, the bonding force between the inner and outer coated layers in the technical solution provided by this invention is significantly enhanced by the preparation method provided by this invention.

[0022] Another aspect of the present invention provides a method for preparing the above-mentioned covered scaffold, which is simple and easy to operate, and specifically includes the following steps: S1: Electrospin the spinning solution onto the outer wall of the adjustable diameter receiving device to form an inner coating; S2: Install the support frame on the receiving device with the inner layer film and adjust the diameter of the receiving device to expand the inner layer film until part of the inner layer film is embedded in the grid of the support frame. S3: Electrospin the spinning solution onto the outer wall of the support skeleton to form an outer coating; S4: After the outer coating is completed, stop electrospinning, reduce the diameter of the cylindrical receiving device and pull it out of the coating support cavity to obtain the coating support.

[0023] According to the preparation method provided by the above technical solution, in step S1 and / or S3, the diameter of the receiving device can gradually increase during the inner coating preparation process, with an increase rate of 0.1-10 mm / h. Further, the diameter increase rate of the receiving device during the inner coating preparation process can be a new range consisting of any two values ​​from 0.1 to 10, such as 0.1-1 mm / h, 1-8 mm / h, 1-6 mm / h, 1-4 mm / h, 3-10 mm / h, 5-10 mm / h, or 7-10 mm / h. The original diameter of the receiving device is 1-50 mm, and more specifically, it can be 1-30 mm. In actual production, a receiving device of the corresponding specification can be matched according to the support of different specifications. Generally, the maximum diameter of the receiving device is 1.2-10 times the minimum diameter (original diameter). When the inner layer coating is first woven in step S1, the diameter of the receiving device can be its minimum diameter or any value between the minimum and maximum diameter. However, it must satisfy that the total diameter of the receiving device and the inner layer coating after the inner layer coating is woven in step S1 is less than the inner diameter of the support frame. At the same time, it must also satisfy that the diameter of the receiving device when the outer layer coating is prepared, i.e., when the operation in step S3 is completed, is 1.2-10 times the diameter before the inner layer coating (i.e. before the operation in step S1).

[0024] According to the preparation method provided by the above technical solution, the depth to which the inner layer coating is embedded in the supporting skeleton grid during textile spinning is 10μm-900μm, including but not limited to 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 200μm, 230μm, 250μm, 280μm, 300μm, 350μm, 500μm, 600μm, 700μm, 800μm, 900μm, etc. Furthermore, the depth to which the inner coating is embedded in the supporting skeleton grid is 10μm-300μm, 10μm-500μm, 10μm-600μm, 10μm-700μm, or 10μm-650μm. Even further, the depth to which the inner coating is embedded in the supporting skeleton grid is 20μm-300μm, 30μm-300μm, 40μm-300μm, or 50μm-300μm.

[0025] According to the preparation method provided by the above technical solution, the spinning solution used in the textile process can be a polymer solution formed by dispersing the polymer in a solvent, or a polymer in a molten state after being melted at high temperature.

[0026] In the preparation method provided by the above technical solution, step S3 includes a step of spraying solvent to dissolve the inner coating before spinning the outer coating. Multiple nozzles can work simultaneously during the spinning of the outer coating. For example, in some embodiments, one nozzle sprays a polymer solution and another sprays a solvent; in other embodiments, one nozzle sprays a solvent and another sprays molten polymer; in still other embodiments, one nozzle sprays a polymer solution and another sprays molten polymer; and in yet another embodiment, one nozzle sprays a polymer solution, another sprays molten polymer, and a third nozzle sprays a solvent. Regardless of the embodiment, the solvent reaches the inner coating before the polymer, achieving the effect of dissolving and softening the fibers in the inner coating before further bonding with the outer coating. Because the polymer sprayed during the spinning of the outer coating further interacts with the dissolved or softened polymer on the inner coating, even undergoing molecular rearrangement, the effect of mutual adhesion is achieved between the multiple layers of the inner coating, between the fibers of the outer coating, and between the multiple layers of the inner and outer coatings.

[0027] In the preparation method provided by the above technical solution, the solvent used to dissolve the inner and outer coatings during spinning is one or more of dichloromethane, trichloromethane, tetrahydrofuran, ethyl acetate, ethanol, isopropanol, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, hexafluoroisopropanol, trifluoroacetic acid, and hexafluoroisopropanol trifluoroethanol. For example, in some embodiments, the solvent used to dissolve the inner coating is dichloromethane, while in other embodiments, the solvent used to dissolve the inner coating is a combination of dichloromethane, ethyl acetate, and hexafluoroisopropanol.

[0028] In the preparation method provided by the above technical solution, the mass ratio of solvent to polymer in the polymer solution dispersed in the solvent is 80:20-99:1, and can further be within the range of 80:20-50:1, 80:20-30:1, 80:20-25:1, 80:20-20:1, 80:20-15:1, etc.

[0029] In the preparation method provided by the above technical solution, when spinning is a polymer melt in a molten state, the viscosity of the spinning is controlled at 10-100 Pa·s, thereby improving the spinning efficiency, reducing the diameter of the spinning, and making the thickness of the inner or outer coating that is finally spun is thinner.

[0030] In the preparation method provided by this invention, the diameter of the inner and outer coated spun fibers is 1-5 μm.

[0031] In some embodiments of the present invention, in order to control the viscosity of melt spinning, a small amount of inorganic salt can be mixed into the polymer to reduce the viscosity of the solution. The inorganic salt selected is one or more of sodium chloride, sodium phosphate, potassium chloride, sodium chloride, magnesium chloride, aluminum chloride, sodium hydrogen phosphate, disodium hydrogen phosphate, calcium phosphate, sodium carbonate, sodium bicarbonate, calcium carbonate, calcium carbonate, ferric chloride, aluminum chloride, ferric hydroxide, ferric chloride, and ferrous gluconate.

[0032] In the preparation method of the film-coated scaffold provided by the present invention, in steps S1 and S3, the electrospinning voltage is controlled at 5-100kV, the polymer injection flow rate is 0.01-1ml / min, the distance between the receiving device and the nozzle is 2-15cm, and the rotation speed of the receiving device is 100-2000 / min, depending on the polymer concentration, viscosity and conductivity.

[0033] The outline of the covered stent in this invention refers to the size of the outer diameter of the covered stent system after the covered stent is pressed onto the support.

[0034] The present invention also provides a receiving device for the above-mentioned preparation method, wherein the diameter of the receiving device is adjustable, and its maximum diameter is 1.2-10 times the minimum diameter.

[0035] The receiving device provided by the above technical solution has a conductive coating and / or a release agent on its surface.

[0036] The receiving device provided by the above technical solution has a microporous structure on its surface, with the diameter of the micropores being 10-100μm and the spacing between the micropores being 0.1-10 mm.

[0037] The receiving device provided by the above technical solution is cylindrical in shape.

[0038] The receiving device provided by the above technical solution is equipped with a heating component, that is, the receiving device is also equipped with a heating function, which can heat the spinning or coating placed on it, thereby accelerating the bonding between the spinning fibers and making the bonding force between the spinning fibers greater and having a greater binding force.

[0039] The receiving device provided by the above technical solution has micropores on its surface in the shape of one or more of the following: strip-shaped, grid-shaped, or disordered scattered dots.

[0040] It should be understood that the terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “described” as used herein may also include the plural forms. The terms “comprising,” “including,” “containing,” and “having” are inclusive and therefore indicate the presence of the stated features, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, and / or combinations thereof. The method steps, processes, and operations described herein are not construed as requiring them to be performed in a particular order described or illustrated unless the order of performance is explicitly indicated. It should also be understood that additional or alternative steps may be used.

[0041] It should be noted that the symbol " / " in this invention represents "or," such as "A / B" meaning "A or B"; or "A and / or B" meaning "A and B, or A or B." Furthermore, the statement in this invention that "the drug includes an anticoagulant and / or an anti-proliferative drug" means that the drug carried on the covered stent includes both an anticoagulant and an anti-proliferative drug, or that the drug carried on the covered stent is one of an anticoagulant and an anti-proliferative drug. That is, the drug carried on the covered stent is at least one of an anticoagulant and an anti-proliferative drug.

[0042] The beneficial effects of this invention are: The coated scaffold prepared in this invention has a support skeleton tightly sandwiched between an inner and outer coating layer. In the area covered by the support skeleton rods, the outer wall of the inner coating layer is bonded to the inner wall of the support skeleton cavity, and the inner wall of the outer coating layer is bonded to the outer wall of the support skeleton. Within the support skeleton grid, the outer wall of the inner coating layer and the inner wall of the outer coating layer are tightly bonded, forming continuous or discontinuous bonding areas, which enhances the bonding strength between the inner and outer coating layers. Simultaneously, to enhance the mechanical properties between the inner and outer coating layers, some areas of the electrospun fiber layers that are in contact with each other are dissolved again by the solvent and then re-coagulated and bonded together, enhancing the bonding force between the fiber layers and the mechanical properties of the coating, making the electrospun layers less prone to delamination. The coated scaffold prepared using this method does not require subsequent high-temperature heating and melting bonding between the spun fibers and the supporting framework, nor does it require the use of adhesives. The coating retains the advantages of electrospun fibers—fine filament diameter, thin coating, and easily adjustable porosity—resulting in a high specific surface area, high porosity, and good elasticity. The coating layer structure easily mimics the composition and structure of the extracellular matrix, which is beneficial for endothelial cell formation and control of neointimal hyperplasia, reducing thrombus formation and improving the long-term efficacy of the coated scaffold. It also has the following advantages: In this invention, the inner coating layer, under the strong support and compression of the receiving device, remains embedded in the grid of the supporting skeleton at a depth of 10-900 μm. Once embedded in the grid of the supporting skeleton, the inner coating layer allows the spinning fibers to adhere well to it during the spinning of the outer coating layer. Further dissolving or melting the inner coating layer with a coating liquid or solvent causes the coating fibers of the inner and outer coating layers of the supporting skeleton to bond together, enhancing the bonding strength between the inner and outer coating layers. Simultaneously, the increased diameter of the receiving device stretches the spinning fibers on the device, and the outer spinning layer exerts a pressure on the inner spinning layer towards the center, resulting in a tighter bond between the spinning fiber layers and smaller gaps, thereby significantly increasing the bonding force between the spinning fiber layers.

[0043] This invention enhances the bonding force between the inner and outer films by changing the bonding method between the inner and outer films, strengthening the interaction force between the inner and outer films during the preparation process, and increasing the contact area between the inner and outer films.

[0044] The coated stent provided by this invention has a very thin coating. First, certain measures are taken during the fabrication process to ensure that the spinning fibers have a small diameter. Second, while ensuring a tight bond between the inner and outer coatings, the gaps between the inner and outer coatings are reduced, increasing the density of the inner and outer coatings, thereby reducing the coating thickness. Finally, during the fabrication of the inner and outer coatings, the diameter of the receiving device is increased while spinning. Combined with control over the rate of increase in the receiving device diameter, the inner and outer coating fibers are brought into close contact. An additional solution spraying step is added, causing the fibers between different spinning layers to dissolve again. After the solvent evaporates, the contacting fibers solidify and bond together again, causing the fibers in certain areas of the coating layer to adhere to each other in the thickness direction, increasing the strength of the spun coating layer, and further reducing the wall thickness of the inner and outer coatings. Combining these three factors, the coated stent ultimately ensures a very small gripping outer diameter after compression, improving the stent's delivery capacity in the body and reducing the risk of damage to human blood vessels. Attached Figure Description

[0045] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Furthermore, the same reference numerals denote the same parts throughout the drawings. Wherein: Figure 1 This is a diagram of a membrane-coated stent structure, where 100 is the membrane-coated stent, 111 is the membrane, 101 is the supporting skeleton, 102 is the inner membrane, and 103 is the outer membrane.

[0046] Figure 2This is a longitudinal cross-sectional view of the absorbable membrane stent in Example 1, where 101 is the absorbable iron-based stent, 102 is the inner membrane, 103 is the outer membrane, 2 is the inner wall of the absorbable iron-based stent, and 3 is the outer wall of the absorbable iron-based stent.

[0047] Figure 3 This is a flowchart illustrating the fabrication process of an absorbable coated scaffold.

[0048] Figure 4 This is a structural diagram of an electrospinning machine.

[0049] Figure 5 This is a cross-sectional view of the inner layer of the absorbable film-coated support on the receiving device in Example 1.

[0050] Figure 6 This is a cross-sectional view of the inner layer of the film-coated support in Example 1 after the absorbable iron-based support is installed on the outside.

[0051] Figure 7 This is a cross-sectional view of the absorbable film-coated stent in Example 1, where 2 is the inner surface of the absorbable iron-based support frame, 4 is the grid area of ​​the support frame, 3 is the outer surface of the absorbable iron-based support frame, 101 is the absorbable iron-based stent, 102 is the inner film layer of the stent, and 103 is the outer film layer of the stent.

[0052] Figure 8 This is an electron microscope image of the coating morphology of the absorbable coated scaffold in Example 1.

[0053] Figure 9 This is a scanning electron microscope image of endothelialization after the absorbable covered stent in Example 1 was implanted into the human body.

[0054] Figure 10 This is a histopathological image of the absorbable covered scaffold implanted in the human body in Example 1.

[0055] Figure 11 The image shows a cross-sectional view of the film-coated stent in Example 2, where 2 is the inner surface of the support frame, 4 is the grid area of ​​the support frame, 3 is the outer surface of the support frame, 201 is the cobalt-chromium alloy stent, 202 is the bottom layer film of the stent, 203 is the inner layer film of the stent, and 204 is the outer layer film of the stent. Detailed Implementation

[0056] Exemplary embodiments of the invention will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of the invention are shown in the drawings, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the invention and to fully convey the scope of the invention to those skilled in the art.

[0057] Please see Figure 1 The diagram shows the structure of a covered stent device 100, which is a tubular structure formed by covering the surface of a hollow support skeleton with a membrane. 100 consists of a support skeleton 101 and a membrane 111 on the support skeleton. The membrane 111 consists of an inner membrane 102 and an outer membrane 103. The inner membrane 102 is positioned within the lumen on the inner wall side of the support skeleton 101, and the outer membrane 103 is positioned on the outer surface of the support skeleton 101. The inner membrane 102 and the outer membrane 103 are bonded together at four points in the grid area of ​​the support skeleton, thus firmly embedding the support skeleton 101 within the membrane layer 111.

[0058] In one embodiment, the support frame 101 can be made of any material; in other embodiments, the support frame is made of a bioabsorbable material. For example, the support frame 101 is made of materials such as iron, iron-based alloys, magnesium, magnesium-based alloys, zinc, zinc-based alloys, or absorbable polymers.

[0059] In one embodiment, the support frame 101 is made of a non-bioabsorbable material. For example, the support frame 101 is made of medical materials such as nickel-titanium alloy, cobalt-chromium alloy, or stainless steel.

[0060] Furthermore, the materials used for the inner and outer coatings are selected from at least one of cellulose, chitin, hyaluronic acid, collagen, gelatin, sodium alginate, polyurethane (PU), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (E-PTFE), polylactic acid (PAL), poly(l-lactic acid) (PLLA), poly(D-lactide) (PDLLA), polyglycolic acid (PGA), polycaprolactone (PCL), polyamide (PA), and polyethylene terephthalate (PET). In some embodiments, the materials used for the inner and outer coatings are one of the aforementioned materials, such as gelatin for the inner coating and sodium alginate for the outer coating. In other embodiments, the inner and outer coatings are prepared from at least two of the aforementioned materials, and can be blends and / or copolymers of at least two or more of the aforementioned materials. That is, they can be simple blends of at least two materials, simple copolymers of at least two materials, or blends and copolymers of at least two of the aforementioned materials. For example, the inner coating is a blend of gelatin and sodium alginate, while the outer coating is a copolymer of polytetrafluoroethylene and polyamide, or the outer coating portion is a copolymer of polytetrafluoroethylene and polyamide. The polymer is partly a blend of polytetrafluoroethylene and polyamide; in some embodiments, the material of the inner coating can be the same as that of the outer coating, such as both the inner and outer coatings being a blend of gelatin and sodium alginate; in some embodiments, the material of the inner coating can also be different from that of the outer coating, such as the inner coating being gelatin and the outer coating being a copolymer of sodium alginate and polyurethane; in other embodiments, the inner and outer coatings can each be multilayer films spun from different materials, such as the bottom layer of the inner coating being collagen or a copolymer of sodium alginate and polyurethane, and the outer layer of the inner coating being gelatin or a copolymer or blend of L-polylactic acid and polyamide, etc.

[0061] In one embodiment, the scaffold coating is prepared using solution electrospinning. Further, during solution electrospinning, the solvent used is one or more mixtures of dichloromethane, trichloromethane, tetrahydrofuran, ethyl acetate, ethanol, isopropanol, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, hexafluoroisopropanol, trifluoroacetic acid, and hexafluoroisopropanol trifluoroethanol to dissolve the polymer. The mass ratio of solvent to polymer in the polymer solution dispersed in the solvent is 80:20-99:1, and can further be within the range of 80:20-50:1, 80:20-30:1, 80:20-25:1, 80:20-20:1, 80:20-15:1, etc.

[0062] In one embodiment, the scaffold coating is prepared using melt electrospinning. Further, during melt electrospinning, the viscosity of the melt is controlled between 10 and 100 Pa·s. Specifically, the viscosity of the melt is adjusted using one or more organic salts selected from sodium chloride, sodium phosphate, potassium chloride, sodium chloride, magnesium chloride, aluminum chloride, sodium hydrogen phosphate, disodium hydrogen phosphate, calcium phosphate, sodium carbonate, sodium bicarbonate, calcium carbonate, calcium carbonate, ferric chloride, aluminum chloride, ferric hydroxide, ferric chloride, and ferrous gluconate.

[0063] In one embodiment, the inner coating is coated using melt electrospinning, and the outer coating is coated using solution electrospinning. Furthermore, both the inner and outer coatings can be coated using a blend of melt spinning and solution spinning, or by alternating spinning processes.

[0064] In one embodiment, an inner lining membrane is added to the inner lining membrane to improve the blood compatibility of the covered stent.

[0065] In one embodiment, an anticoagulant is loaded into the inner lining of the stent to prevent thrombus formation within the stent. The anticoagulant is selected from one or more of heparin, hirudin, sodium citrate, EDTA, aspirin, warfarin, and rivaroxaban. Specifically, a sufficient amount of the anticoagulant is incorporated into the lining material and then subjected to liquid electrospinning or melt electrospinning to load the anticoagulant into the spun fibers, achieving a slow release that inhibits thrombus formation within the stent.

[0066] In one embodiment, the outer coating contains an anti-proliferative drug selected from one or more of sirolimus, tacrolimus, pimecrolimus, paclitaxel, colchicine, dexamethasone, prednisone, and hydrocortisone. Specifically, a sufficient amount of the anti-proliferative drug is incorporated into the coating material, and the mixture is then subjected to liquid electrospinning or melt electrospinning to load the anti-proliferative drug into the spun fibers, thereby achieving the purpose of slow release to inhibit excessive proliferation of the newly formed endometrium.

[0067] In one embodiment, the outer film completely covers the support frame; in another embodiment, the outer film only partially covers the support frame, covering an area of ​​10%-100% along the radial length of the support frame.

[0068] The fabrication process of covered stent devices includes the following steps: S1. An adjustable-diameter cylindrical receiving device is used as the electrospinning receiving device. An inner layer coating of the support structure is prepared using electrospinning on its outer diameter. Before spinning, the diameter of the receiving device is adjusted to the required size, ensuring that the total diameter of the receiving device plus the inner layer coating thickness is smaller than the inner diameter of the support skeleton requiring coating. At least one polymer solution spinning nozzle and one solvent nozzle are arranged above the cylindrical receiving device. During electrospinning, the polymer solution nozzle and solvent nozzle are connected to the positive terminal of a power generator, and the negative terminal is connected to the cylindrical receiving device. The power supply is turned on and the voltage is adjusted. The flow rate of the syringe, the distance between the cylindrical receiving device and the nozzle, and the rotation speed of the receiving device are also adjusted. Finally, under the action of electrostatic force, the polymer solution forms electrospun fibers that are sprayed onto the rotating cylindrical receiving device. Because the solvent in the solvent nozzle has a lower viscosity than the polymer spinning solution, under the same electrostatic attraction, the solvent forms tiny droplets that fly towards the electrospinning bundle on the receiving device. The spindle fibers around the solvent droplets are dissolved again, and after the solvent evaporates, they solidify again. The spindle fibers that come into contact with each other at the droplet point adhere together, forming a disordered arrangement that creates an inner layer coating of the support structure that is bonded together in the thickness direction. Furthermore, the distance between the solvent nozzle and the receiving device can be reduced to allow the solvent jet to be sprayed directly and continuously onto the spindle bundle, forming a continuously oriented spindle adhesion zone.

[0069] Specifically, the diameter-adjustable receiving device can be an adjustment mechanism with a mechanical structure or a balloon expansion adjustment mechanism. The mechanically designed receiving device allows diameter adjustment simply by rotating the expansion mechanism. The balloon expansion adjustment receiving device allows balloon diameter adjustment simply by injecting the same volume of liquid or gas into the balloon. Furthermore, the diameter adjustment method can be step-by-step or incremental. The original diameter of the diameter-adjustable cylindrical receiving device is 1-50 mm, and the diameter adjustment range is 1.01-10 times the original diameter, preferably 1.5 times. In step-by-step increments, the diameter increases by 0.05-1 mm per step, preferably 0.1 mm. In incremental increases, the diameter increase rate is 0.1-10 mm / h, preferably 1 mm / h.

[0070] In one embodiment, the diameter-adjustable receiving device may also have a microporous structure on its surface. The perimeter of the inner coating layer projected by the micropores is 30-300 μm, preferably 100 μm, and the spacing between the micropores is 0.1-10 mm, preferably 1 mm. Specifically, the micropores are selected from one or more combinations of circular, elliptical, polygonal, and irregular shapes. Further, the arrangement of the micropores may be one or a combination of strip-shaped, grid-shaped, or disordered scattered dots. During electrospinning, the micropores can conduct away the charge on the electrospinning wire, reducing the accumulation of charge on the wire and reducing the mutual repulsion between the wires.

[0071] In one embodiment, the surface of the cylindrical receiving device with an adjustable diameter is covered with a flexible material. When the diameter is increased, the flexible material on the surface of the receiving device, along with the inner layer film, is pressed inward in the area bound by the supporting frame rod. In the support grid area, the flexible material on the surface of the receiving device, along with the inner layer film, is pressed into the support frame grid, embedding the inner wall layer film onto the support frame. Specifically, the flexible material is selected from natural rubber, butyl rubber, cis-butadiene rubber, neoprene rubber, EPDM rubber, acrylic rubber, polyurethane rubber, conductive silicone rubber, nylon, polyester, acrylic polyester fiber, aramid, polypropylene fiber, PET, and PTFE. Further, the indentation depth of the flexible material on the surface of the receiving device due to the pressure of the supporting frame rod is 10-200 μm, and the height of the protrusion into the grid in the support frame grid area is 10-900 μm.

[0072] In one embodiment, the cylindrical receiving device with adjustable diameter is provided with rigid protrusions of different shapes on its surface. When the diameter of the receiving device is increased, the rigid protrusions press the inner layer of the support into the grid area. The height of the rigid protrusions is 1-100μm, and the pattern area of ​​the rigid protrusions accounts for 10%-90% of the total rod surface. Furthermore, the rigid protrusion pattern can be a uniform or non-uniform distribution of dots, or a continuous strip or grid pattern, or a protrusion pattern that matches the shape of the support grid.

[0073] In some embodiments, further, in step S1, after spinning several layers of spun fibers, the diameter of the cylindrical receiving device can be increased by a certain size, so that the coated spun fibers on the cylindrical receiving device are in a taut state in the circumferential direction. At this time, the outer layer of the coated spun fibers will exert pressure on the inner layer of the spun fibers, reducing the gap between the spun fibers and facilitating the re-dissolved spun fibers to stick together.

[0074] Furthermore, in step S1, depending on the polymer concentration, viscosity, and conductivity, the electrospinning voltage is 5-100kV, the injection flow rate is 0.01-1ml / min, the distance between the receiving device and the nozzle is 2-15cm, and the rotation speed of the receiving device is 100-2000 / min.

[0075] Furthermore, in step S1, there can be one or more polymer nozzles. They can be a solution spinning nozzle, a melt spinning nozzle, or a blended nozzle that combines solution spinning and melt spinning.

[0076] Furthermore, in step S1, the distance between the solvent nozzle and the receiving device is 1-5 cm, and the liquid is directly jetted onto the spinning process, forming a continuous solvent imprint on the spinning coating layer. Alternatively, the distance between the solvent nozzle and the receiving device can be increased to 5-10 cm, and the solvent liquid forms dispersed droplets that are sprayed onto the spinning bundle on the coating layer. The solvent injection flow rate is 0.01-0.5 ml / min. The solvent injection can be continuous or pulsed injection at certain intervals, with a pulse interval of 0.1-100 s.

[0077] S2. After the inner layer of the support is prepared, the support frame to be coated is fitted onto the receiving device covered with the inner layer of the film. The diameter of the receiving device is enlarged, and the inner layer of the film is pressed tightly against the inner wall of the support frame by the receiving device. The film below the support frame rod is in close contact with the inner wall side of the support frame rod, and the inner layer of the film at the grid part of the support frame rod is pressed and protrudes into the grid of the support.

[0078] S3. Continue to prepare an outer wall layer coating on the outside of the support skeleton using the method described in S1.

[0079] S4. After the outer layer coating is completed, stop the spinning equipment, reduce the diameter of the cylindrical receiving device and pull it out of the coating support to obtain the coating support with the inner and outer walls coated at the same time.

[0080] The following specific embodiments further illustrate the above-mentioned covered stent device and its preparation method.

[0081] The testing methods used in this embodiment are as follows: 1. Morphological analysis The morphology of the coating on the coated scaffold was observed using a scanning electron microscope (SEM). The diameter of the wire was measured at 2000x magnification. The SEM used was a JSM6510 scanning electron microscope from Nippon Electron Ltd.

[0082] 2. Porosity testing The porosity of the coated scaffold was tested in accordance with GB / T33052-2016, "Method for Determination of Porosity of Microporous Functional Thin Films - Hexadecane Absorption Method".

[0083] 3. Porosity between the inner and outer coating layers: The coated support structure was expanded to its nominal diameter and then embedded in plexiglass. It was then cut transversely, and the cross-section was smoothed using diamond sandpaper of different grit sizes. The sum of the arc lengths of the gaps on both sides of all the support struts between the inner and outer coatings was measured using a microscope. L 空隙 And the circumferential arc length L of the supporting skeleton 圆周 Then, the porosity A of the coating layer was calculated according to the following formula. The microscope used was a Keyence VHX-700F.

[0084] A= ×100% 4. Coating peel strength test The covered stent is longitudinally cut and trimmed to a certain width. A universal tensile testing machine is used to measure the peel strength of the inner and outer layers of the covered stent. Taking the peel strength test of the inner and outer layers of the superficial femoral artery covered stent as an example, the specific steps include: After longitudinally cutting the coated support frame into strips 10mm wide and 10cm long, peel off the inner and outer coating layers from one end, leaving a length of approximately 5cm. Adjust the distance between the upper and lower clamps of the universal tensile testing machine to approximately 5cm. Clamp the peeled inner coating layer of the support frame in the upper clamp and the outer coating layer in the lower clamp. Set the tensile movement speed to 10mm / min. At the end of the test, set the parameters (constant force decay) to 50%. Start the test to test the maximum coating peeling force N. Calculate the coating peel strength P of the inner and outer walls of the coated support frame using the following formula: P=N / L, where P is the peel strength in N / mm; N is the maximum tensile force of the coating peel in N; and L is the sample width in mm.

[0085] 5. Grip outer diameter of the film-coated stent The gripping outer diameter of the covered scaffold was tested using a microscope. The microscope used was either a Keyence VHX-700F or a Sensofaras Q6.

[0086] 6. Coating thickness test The coated support was embedded in plexiglass, cut horizontally or vertically, and polished smooth with diamond sandpaper of different grit sizes. The thickness of each coating layer was then measured using a microscope. The microscope used was either a Keyence VHX-700F or a Sensofaras Q6.

[0087] 7. Test of Endothelialization Rate of Absorbable Covered Scaffold Taking the evaluation of endothelialization after implantation of a endothelial stent in the superficial femoral artery in miniature pigs as an example, a endothelial stent was implanted in the superficial femoral artery of 6 miniature pigs weighing 30-35 kg. After 7, 14 and 28 days of implantation, the pigs were euthanized and the implanted stent segment was removed. After fixation with 2.5% glutaraldehyde for 72 hours, the stent was cut in half longitudinally and then dehydrated in a gradient of 80%, 90%, 95%, 95% and 100% ethanol concentrations, followed by critical point drying with carbon dioxide. After gold sputtering, SEM scanning was performed to calculate the ratio of the area covered by neointimacy of the entire endothelial stent. Endothelial coverage rate = (area of ​​endothelial-covered area / total surface area of ​​the stent) × 100%.

[0088] 8. Pathological reactions after implantation Taking the assessment of tissue response after implantation of a femoral artery covered stent in miniature pigs as an example, a femoral artery covered stent was implanted into the femoral artery of three miniature pigs weighing 30-35 kg. Twenty-eight days after implantation, the animals were euthanized and the covered stent was removed. The stent was fixed with 10% formaldehyde for 7 days, then dehydrated with a series of 70%, 80%, 90%, and 100% alcohols. The stent was then embedded in methyl methacrylate resin and cured. After curing, sections were prepared using a precision cutting machine (BUEHLER Lsomet 5000, USA) to a thickness of approximately 150 μm. The sections were then polished thinner using a polishing machine (BUEHLER Econet 250, USA) to a thickness of approximately 10-20 μm. Hematoxylin staining was performed for 30 min, differentiation with differentiation solution for 1 min, ammonia blue staining for 10 min, and eosin staining for 5 min to prepare pathological sections. Histopathological examination was conducted using a LEICA DM2500 microscope (Germany), and the luminal area of ​​the stent segment and the original luminal area were measured. Therefore, the stenosis rate is calculated as follows: (Original lumen area - Current lumen area) / Original lumen area × 100% Example 1 The longitudinal cross-sectional view of the absorbable covered stent 100 provided in this embodiment is as follows: Figure 2 As shown, the absorbable membrane-coated support 100 consists of a support frame 101, an inner membrane 102 on the support frame, and an outer membrane 103 on the support frame. The inner membrane 102 is positioned within the lumen of the support frame 101, and its outer wall surface is in close contact with the inner wall 2 of the support frame 101. The outer membrane 103 is positioned on the outer surface of the support frame 101, and its inner wall surface is in close contact with the outer wall 3 of the support frame 101. The inner membrane 102 and the outer membrane 103 are bonded together at the grid area 4 of the support frame, thereby firmly embedding the support frame 101 in the middle of the membrane layer 111. In this embodiment, the supporting skeleton 101 is an absorbable iron-based alloy stent, made of 99% nitrided pure iron through nitriding and laser engraving. The nitrogen content of the nitrided pure iron is ≤0.25%. The stent has a nominal expansion diameter of 6mm and consists of 10 sets of corrugated coils and connecting rods. The stent rod wall thickness is 80μm, and the radial support force is 120kPa. The inner layer coating 102 and the outer layer coating 103 of the stent are made of PLLA liquid electrospinning, with a total thickness of 69.8μm. The absorbable coated stent is pressed onto the expansion balloon, with a pressing outer diameter of 1.8mm. The fabrication steps of the coated stent are as follows: Figure 3 As shown.

[0089] Step S1: Prepare the inner wall coating 102. Add 10g of PLLA with a molecular weight of 500,000 to 190ml of ethyl acetate, and stir at room temperature in a sealed container for 8 hours until completely dissolved, obtaining a 5% (w / w) polylactic acid spinning solution. (Refer to...) Figure 4Set up an electrostatic spinning machine. First, the polylactic acid spinning solution is drawn into a micro-injection pump 35 and connected to the spinning solution nozzle 37 via a micro-catheter. The distance between the spinning solution nozzle 37 and the cylindrical receiving device 30 is set to 10 cm. The rotation speed of the receiving device 30 is 200 rpm, and the axial reciprocating speed is 0.1 mm / s. The pump flow rate of the spinning solution 35 is 0.05 ml / min. Separately, trichloromethane is added to a solvent injector 36, and the pump flow rate is adjusted to 0.1 ml / min. The injection pulse interval is set to 10 s, and the duration is 6 s. The solvent nozzle 41 and the receiving device... The receiving device 30 was positioned 5 cm away from the electrospinning power supply 40, and the voltage was adjusted to 15 kV. The equipment was then turned on to prepare the inner layer coating of the scaffold. During the spinning process, the diameter of the receiving device 30 was increased by 0.1 mm every 30 minutes. This increase in diameter caused the spun fibers on the surface to be radially stretched, resulting in mutual compression between the fibers and reducing the gaps between them. Solvent fell onto the tightly contacting fiber bundles, and under the solvent's dissolving effect, the fibers at the solvent droplets were dissolved. After the solvent completely evaporated, the tightly contacting fibers bonded together. Electrospinning for 60 minutes yielded a 27.6 μm thick oriented spun coating, i.e., the inner wall coating 102 of the scaffold. Figure 5 As shown.

[0090] In this embodiment, the cylindrical receiving device 30 with a variable diameter is a balloon ( Figure 5 The balloon structure is simple and easy to operate; its diameter can be changed simply by injecting different volumes of liquid. A small amount of saturated sodium chloride solution is injected into the receiving device 30, filling it to a diameter of 4.5 mm. The negative terminal 39 of the power supply of the electrospinning machine 40 is connected to the saturated sodium chloride solution 29 inside the balloon, and the positive terminal 38 of the power supply is connected to the polymer solution nozzle 37 and the solvent nozzle 41. An electric field E2 is formed between the liquid in the balloon and the polymer nozzle 37, which powers the polymer to form electrospinning. An electric field E1 is formed between the liquid in the balloon and the solvent nozzle 41, which powers the solvent jet.

[0091] Step S2: Load the absorbable iron-based alloy stent. Install the absorbable iron-based alloy stent 101 on the outer periphery of the inner layer membrane 102 of the stent. Continue to inject saturated sodium chloride solution 29 into the receiving device 30. The outer diameter of the receiving device 30 gradually increases to 5.0 mm, pressing the inner layer membrane 102 into the inner cavity of the stent. The outer side of the inner layer membrane 102 is tightly attached to the inner surface 2 of the absorbable iron-based alloy stent 101. The inner layer membrane 102 at the grid area 4 of the stent is pressed into the grid area 4 of the stent by the balloon and protrudes 80 μm above the inner wall of the stent rod. Figure 6 As shown; Step S3 involves the preparation of the outer coating. Following the same method as the inner coating preparation, electrospinning is used to obtain the outer coating 103 on the outer wall of the absorbable iron-based alloy scaffold 101. During the outer coating process, solvent droplets sprayed from the solvent nozzle dissolve some of the spun fibers in both the inner and outer coatings. After solvent evaporation, the inner coating 102 and outer coating 103 come into contact and bond together at the mesh structure unit 4 of the scaffold, forming a strong bond. The inner side of the coating 103 is tightly adhered to the outer surface 3 of the absorbable iron-based alloy scaffold 101, achieving the goal of firmly embedding the absorbable iron-based scaffold in the middle of the membrane layer. The outer coating conditions are the same as the inner coating conditions. Electrospinning for 120 minutes yields a total membrane thickness of 69.8 μm. Figure 7 As shown.

[0092] In step S4, the covering is trimmed. Saturated sodium chloride solution 29 is withdrawn from balloon 30, reducing the diameter of balloon 30 and causing it to detach from the inner covering. The covered stent 100 is removed from the balloon, and excess covering at both ends is trimmed. The covered stent is then compressed onto the balloon dilation catheter, with an outer diameter of 1.8 mm. After packaging in a dialysis bag and sterilizing with EO (epoxy ethane), the final absorbable covered stent product 100 is obtained. In clinical use, the covered stent is simply delivered to the diseased blood vessel, and pressure is applied to the balloon to expand the covered stent, completing the implantation treatment. The covered stent, polylactic acid covering, and iron-based alloy stent will slowly degrade and be absorbed in the body, eventually restoring the blood vessel's natural curvature and constriction, leaving no residual implant in the vessel.

[0093] The aforementioned detection methods showed that the absorbable coated scaffold exhibited good spinning orientation, good uniformity in spinning diameter (1.5-2 μm), and visible adhesion between the spinning fibers. Figure 8 As shown. The coating layer maintains a high porosity, which was tested to be 82%. The inner and outer coating layers have strong adhesion, and the absorbable iron-based scaffold is firmly fixed in the coating layer. The total thickness of the inner and outer coating layers is 72 μm, and the gripping diameter on the expansion balloon is 2.3 mm. The bonding strength between the inner and outer coating layers is 0.3 N / mm, and the peel strength of the outer coating layer is 0.12 N / mm. The total arc length of the gaps between the inner and outer coating layers is very small, accounting for only 1.2% of the total arc length of the circumference of the cross-section.

[0094] Endothelialization rate and tissue response of absorbable covered stents were assessed after implantation in the superficial femoral artery of miniature pigs. At 7 days post-implantation, neointimal coverage was 67±15%, with atypical endothelial cell morphology on the covered surface. At 14 days post-implantation, neointimal coverage was 90±5%, with morphologically typical endothelial cells visible. At 28 days post-implantation, neointimal coverage reached 100%, and the luminal surface of the covered stent was covered with morphologically typical endothelial cells. Figure 9 As shown.

[0095] Histopathological examination 28 days after implantation showed that all tissue cells had grown into the graft, with no inflammatory reaction or cell necrosis around the graft. The absorbable graft showed good tissue compatibility and no significant neointimal hyperplasia. The vascular stenosis rate, measured using the aforementioned detection methods, was 21%. Figure 10 As shown.

[0096] Example 2 In this embodiment, an inner layer membrane is added on top of the inner membrane to enhance the antithrombotic ability of the covered stent. Figure 11 The cross-section of the covered stent 200, which has good blood compatibility, is shown. The covered stent 200 consists of a cobalt-chromium alloy supporting framework stent 201, a bottom layer cover 202, an inner layer cover 203, and an outer layer cover 204. The bottom layer cover 202 is positioned on the inner wall of the lumen of the inner layer cover 203. The inner layer cover 203 is positioned within the lumen of the cobalt-chromium alloy supporting framework stent 201 and on the outer wall of the bottom layer cover 202, and is in close contact with the inner surface 2 of the cobalt-chromium alloy supporting framework stent 201. The outer layer cover 204 is positioned on the outer surface of the cobalt-chromium alloy supporting framework stent 201 and is in close contact with the outer surface 3 of the stent 201. The inner layer cover 203 and the outer layer cover 204 are bonded together at the stent grid area 4. In this way, the cobalt-chromium alloy supporting framework stent 201 is firmly embedded between the outer layer cover and the inner layer cover, and the outer layer cover 100% covers the cobalt-chromium alloy supporting framework 201. In this embodiment, the coated scaffold 200 has a nominal expansion diameter of 10 mm, the cobalt-chromium alloy support frame 201 has a wall thickness of 120 μm, and is a tubular body composed of 5 sets of beaded coils and connecting rods. The bottom coating 202 is 5 μm thick, and the inner coating 203 and outer coating 204 are made of PET (Polyethylene terephthalate) melt electrospinning. The total thickness of the inner and outer coatings is 120 μm, and the spinning diameter is about 4 μm. The fabrication steps are as follows: First, a 5 μm thick PTFE film is covered on the diameter-adjustable receiving device, and then the inner and outer coatings of the scaffold are prepared by melt spinning. First, the diameter of the adjustable receiving device is set to 9.0 mm, then a PTFE film with a thickness of 5 μm is applied, and then the inner layer coating is prepared. In this embodiment, the diameter of the adjustable receiving device is adjusted by a mechanical structure.

[0097] S1 Inner Layer Coating Preparation: Weigh 20mg of PET raw material chips and add them to a spinneret tube equipped with heating, extrusion, and stirring functions. Simultaneously, mix in 5% sodium chloride powder to reduce the viscosity of the melt. Heat the raw material to melt using electric heating. The melt heating temperature is set to 270°C, the spinning environment temperature is set to 65°C, the distance between the spinneret and the receiving device is 7 cm, the rotation speed of the receiving device is 100 / min, the spinning voltage is 25 kV, and the feeding pressure is 2 kPa. Prepare the inner layer coating 203 of the support on the outer wall of the bottom layer coating 202. Increase the diameter of the receiving device by 0.1 mm every 15 min of spinning. After 60 min of electrospinning, obtain a 51.3μm thick oriented inner wall coating of the support. In this embodiment, the temperature of the receiving device is set to 90°C, which increases the adhesion between the spinning and the bottom layer coating 202 and the adhesion between the spinning fibers.

[0098] S2 Support Frame Installation: After the inner layer film 203 of the support is woven, the cobalt-chromium alloy support frame 201 is expanded to an inner diameter of 10mm and installed on the outer periphery of the inner layer film 203. Then, the diameter of the receiving device is increased until the inner layer film 203 is pressed into the grid area 4 of the support and protrudes 150μm above the inner wall of the support rod.

[0099] S3 Outer Coating Preparation: Following the same method as the inner wall coating preparation method for the cobalt-chromium alloy support skeleton 203, melt electrospinning was performed on the outer wall coating 201 to obtain an outer wall coating with a thickness of 98.5 μm. In this embodiment, the outer coating completely covers the cobalt-chromium alloy support skeleton. During the spinning process, the compression of the inner wall receiving device, the increase in ambient temperature, and the increase in the temperature of the receiving device all contribute to the bonding of the inner and outer coatings in the grid area of ​​the cobalt-chromium alloy stent, ultimately resulting in a coated stent 200 with good blood compatibility.

[0100] Testing revealed that the total thickness of the inner and outer membrane layers of the stent was 149.6 μm, the fiber diameter of the inner and outer membrane layers was 3.8 μm, the peel strength between the inner and outer membrane layers was 0.23 N / mm, the peel strength between the individual spun layers of the inner and outer membrane layers was 0.11 N / mm, the total arc length of the gaps between the inner and outer membrane layers accounted for only 3% of the arc length of the entire cross-section, and the porosity of the membrane was 75%. The clamping diameter of the membrane-coated stent on the dilatation balloon was 3.5 mm.

[0101] Example 3 In this embodiment, the covered stent is an absorbable covered stent whose supporting skeleton is composed of several unconnected wave rings. The supporting skeleton only maintains the radial diameter in the covered stent and does not restrict the axial direction of the covered stent. This makes the covered stent compliant and adaptable to curved blood vessels when implanted. The inner covered stent is less prone to wrinkling and the fatigue performance of the covered stent in curved blood vessels is also improved. The specific preparation method is as follows.

[0102] After preparing a polylactic acid spinning solution with a mass fraction of 8%, the initial diameter of the receiving device was set to 2.5 mm, the rotation speed to 100 rpm, the axial reciprocating speed to 0.1 mm / s, the spinning solution pump flow rate to 0.05 ml / min, the distance between the spinning nozzle and the receiving device to 10 cm, and the voltage to 8 kV. After spinning for 120 min, an inner layer coating with a thickness of 19.9 μm was obtained.

[0103] After the inner coating is prepared, the wave coil ring of the absorbable support skeleton is placed on the outside of the inner coating. The distance between two adjacent wave coil rings of the support skeleton is 4 mm. After all the wave coil rings of the support skeleton are installed, the diameter of the receiving device is adjusted to 3 mm. At this time, except for the inner coating under the wave coil ring rod area of ​​the support skeleton, the inner coating of other parts protrudes from the support skeleton rod and is at least 70 μm higher than the inner wall of the support skeleton.

[0104] The outer coating of the scaffold was prepared using melt spinning. 10 mg of PLA raw material slices were added to a spinneret tube equipped with heating, extrusion, and stirring. The raw material was heated to melt using electric heating, with the melt temperature set at 200°C. Sodium phosphate was mixed in to adjust the PLA melt viscosity to 20 Pa·s. The ambient temperature was set at 45°C, the distance between the spinneret and the receiving device was 7 cm, the spinning voltage was 15 kV, and the feeding pressure was 5 kPa. Electrospinning was performed for 60 min to obtain a 30.3 μm thick outer coating of the scaffold. The resulting blended coated scaffold of this embodiment exhibited discontinuous support skeletons and good flexibility.

[0105] The total thickness of the stent coating, as tested using the aforementioned methods, is 50.1 μm. The peel strength between the inner and outer layers of the stent coating is 0.11 N / mm, and the peel strength between the individual spun layers of the inner and outer layers is 0.02 N / mm. The total arc length of the gap between the inner and outer layers accounts for only 0.7% of the arc length of the entire cross-section, and the porosity of the coating is 90%. The clamping diameter of the coated stent on the dilatation balloon is 1.5 mm.

[0106] Example 4 The covered stent of this embodiment has an inner layer covered with an anticoagulant to prevent thrombosis within the stent, and an outer layer covered with an anti-cell proliferation drug to inhibit excessive neointimal hyperplasia. The specific implementation process of this embodiment is as follows: First, 10g of PLLA with a molecular weight of 300,000 was added to 190ml of ethyl acetate, followed by 500U of heparin sodium injection. The mixture was stirred at room temperature under sealed conditions for 8 hours until completely dissolved, yielding a 5% polylactic acid-heparin spinning solution. A cylindrical receiving device with a flexible PTFE gasket was used. The distance between the receiving device and the spinning nozzle was set to 12cm, the diameter of the receiving device was 2.5mm, the rotation speed was 2000 rpm, the spinning solution pump flow rate was 0.05ml / min, and the spinning voltage was 7kV. Electrospinning was then used to prepare the inner layer coating of the film-coated scaffold. After 120 minutes, a 27.5μm inner layer coating was obtained.

[0107] An absorbable iron-based support is installed outside the inner coating. The diameter of the receiving device is adjusted to 3.4 mm. At this point, the flexible PTFE gasket under the grid of the absorbable iron-based support pushes the inner coating out of the support grid. The flexible PTFE gasket under the support rod, along with the inner coating, is compressed and recessed into the receiving device. The recess depth is 30 μm, and the height of the protrusion into the grid in the grid area is greater than 75 μm.

[0108] Next, an outer coating containing rapamycin was spun on the outer wall of the scaffold. Before spinning the outer coating, 10g of PLLA with a molecular weight of 300,000 was added to 190ml of ethyl acetate, and then 5mg of rapamycin was added. The mixture was stirred at room temperature for 8 hours until completely dissolved, resulting in a 5% polylactic acid-rapamycin spinning solution. The flow rate of the filament solution was pumped at 0.09ml / min, and the voltage was adjusted to 14kV. Other conditions were the same as those for spinning the inner coating of the scaffold. The outer coating of the scaffold was then spun, and after 75 minutes, a 50.7μm thick outer coating containing rapamycin was obtained.

[0109] The total thickness of the stent coating was 78.3 μm, the peel strength between the inner and outer layers of the coated stent was 0.13 N / mm, the peel strength between the multiple layers of the inner and outer coatings was 0.14 N / mm, the total arc length of the gap between the inner and outer coatings accounted for only 0.5% of the arc length of the entire cross-section, the porosity of the coating was 80%, and the gripping diameter of the coated stent on the dilatation balloon was 1.5 mm.

[0110] Example 5 In this embodiment, the coated scaffold contains an X-ray radiopaque material in the coating layer, enhancing the radiopigmentability of the coated scaffold. Its fabrication process is as follows: After preparing a polylactic acid spinning solution with a mass fraction of 8%, the diameter of the receiving device was set to 9.5 mm, the rotation speed to 100 rpm, the axial reciprocating speed to 0.1 mm / s, the pump flow rate of the spinning solution was set to 0.05 ml / min, the distance between the spinning nozzle and the receiving device was set to 10 cm, and the voltage was set to 8 kV. After spinning for 120 min, an inner layer coating with a thickness of 19.5 μm was obtained.

[0111] The iron-based absorbable support frame is placed over the inner coating, and the diameter of the receiving device is adjusted to 10 mm. At this time, except for the inner coating under the wave ring rod area of ​​the support frame, the inner coating of other parts protrudes from the support frame rod and is at least 150 μm higher than the inner wall of the support frame.

[0112] The outer coating of the scaffold was prepared using melt spinning. 10 mg of PLA raw material slices were added to a spinneret tube equipped with heating, extrusion, and stirring. The raw material was heated to melt using electric heating, with the melt temperature set at 200°C. At the same time, 4% (by mass) of barium sulfate powder was mixed into the melt. The ambient temperature was set at 50°C, the distance between the spinneret and the receiving device was 7 cm, the spinning voltage was 15 kV, and the feeding pressure was 10 kPa. Electrospinning of the outer coating for 80 min yielded a 43.4 μm thick radiopaque outer coating of the scaffold, resulting in the X-ray radiopaque scaffold of this embodiment.

[0113] The stent membrane was clearly visible under X-ray using the aforementioned testing methods. The total thickness of the stent membrane was 62.8 μm. The peel strength between the inner and outer membrane layers of the membrane was 0.10 N / mm. The peel strength between the multiple layers of the inner and outer membrane layers was 0.02 N / mm. The total arc length of the gap between the inner and outer membrane layers accounted for only 1% of the arc length of the entire cross-section. The porosity of the membrane was 75%. The clamping diameter of the membrane stent on the dilatation balloon was 3.6 mm.

[0114] Comparative Example 1 This comparative example uses the same spinning conditions as Example 1 to prepare the inner and outer coatings of the scaffold. The difference from the example is that the diameter of the receiving device remains constant whether spinning the inner or outer coating of the scaffold. During the spinning process, no solvent is sprayed to dissolve the spun fibers. All other conditions are the same. Finally, a coated scaffold of Comparative Example 1 with a nominal diameter of 5 mm, an inner coating thickness of 31.5 μm, and an outer coating thickness of 42.3 μm was prepared. It was then pressed onto the expansion catheter for subsequent comparative tests.

[0115] Using the aforementioned testing method, the inner and outer layers of the film-coated scaffold in Comparative Example 1 separated from the supporting skeleton immediately after being pressed together. The total arc length of the gap between the inner and outer film layers occupied the entire circumference of the cross-section, the porosity of the film was 87%, and the peel strength of the multilayer spun outer film was only 0.0052 N / mm, indicating extremely low film layer adhesion strength. Compared with the absorbable film-coated scaffold of Example 1, the peel strength of the inner and outer film layers and the peel strength of the film layer of the absorbable film-coated scaffold in Comparative Example 1 were significantly lower than those of the absorbable film-coated scaffold in Example 1.

[0116] Comparative Example 2 This comparative example uses the same spinning conditions as Example 2, and uses melt spinning to prepare a coated scaffold with a bottom layer coating. The difference from Example 2 is that the diameter of the receiving device remains constant whether the inner layer of the scaffold is coated or the outer layer is coated. Apart from this, all other conditions are the same as in Example 2, and the coated scaffold of Comparative Example 2 with a bottom layer coating is finally prepared.

[0117] Using the aforementioned testing methods, the peel strength between the inner and outer layers of the coated stent in Comparative Example 1 was 0.007 N / mm, and the peel strength between the multiple layers of the inner and outer coatings was 0.009 N / mm. The total arc length of the stent voids accounted for 67% of the arc length of the entire cross-section, and the porosity of the coating was 80%. The gripping diameter of the coated stent on the dilatation balloon was 2.3 mm. Compared with the coated stents prepared in Examples 2, the coating bonding force and peel strength of the coated stent in Comparative Example 2 were both lower than those of the coated stent prepared in Example 2, and the porosity was significantly higher than that of the coated stent prepared in Example 2.

[0118] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A membrane-coated scaffold, comprising an inner membrane, an outer membrane, and a support frame located between the inner and outer membranes, characterized in that, In the support skeleton grid area, the inner layer of the film-coated support is pressed into the support skeleton grid and bonded to the outer layer of the film in the support skeleton grid area without the introduction of adhesive; the inner layer of the film and the outer layer of the film are formed on the receiving device by electrospinning process, and the diameter of the receiving device gradually increases during the film preparation process of the inner layer of the film and / or the outer layer of the film.

2. The covered stent according to claim 1, characterized in that, The peel strength between the inner and outer coating layers is 0.1-0.5 N / mm; the peel strength between the spinning fiber layers in the inner or outer coating layers is 0.01-0.2 N / mm.

3. The covered stent according to claim 1, characterized in that, The thickness of the outer coating is greater than that of the inner coating; the thickness of the outer coating is 1.1-5 times that of the inner coating; at any cross-section along the circumferential direction of the supporting frame, the total arc length of the gap between the inner and outer coatings accounts for 0.1%-5% of the circumferential arc length of the entire cross-section.

4. The covered stent according to claim 1, characterized in that, The thickness of the inner coating is 10-100 μm; the total wall thickness of the inner and outer coatings in the supporting skeleton grid is 30-500 μm.

5. The covered stent according to claim 1, characterized in that, The outer diameter of the covered stent gripping the dilatation balloon catheter is 0.9-6 mm; the porosity of the inner and outer covering layers is 70%-90%.

6. The covered stent according to claim 1, characterized in that, The inner membrane is embedded in the support skeleton grid to a depth of 10-350 μm; the porosity of the inner and outer membranes is 70-85%; the outer diameter of the membrane-covered stent gripping the dilatation balloon catheter is 0.9-5 mm.

7. The covered stent according to claim 1, characterized in that, The materials used for the inner and outer coatings are selected from at least one of cellulose, chitin, hyaluronic acid, collagen, gelatin, sodium alginate, polyurethane, polylactic acid, polyglycolic acid, polycaprolactone, polyamide, and polyethylene terephthalate; the porosity of the inner and outer coatings is 75-88%; the depth to which the inner coating is embedded in the supporting skeleton grid is 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 200μm, 230μm, 250μm, 280μm, 300μm, 350μm, or 500μm.

8. The covered stent according to claim 1, characterized in that, The inner layer of the membrane-coated scaffold completely covers the support skeleton; the outer layer covers 10%-100% of the area along the radial length of the support skeleton; and the inner layer is embedded in the support skeleton grid to a depth of 40-300 μm.

9. The covered stent according to claim 1, characterized in that, The covered stent carries a drug or radiopaque material; the outer diameter of the covered stent gripping the dilating balloon catheter is 0.9-4.5 mm.

10. The covered stent according to claim 1, characterized in that, The supporting frame is either spherically expanding or self-expanding; the supporting frame is either biodegradable or non-biodegradable.

11. The covered stent according to claim 1, characterized in that, The inner coating completely covers the support frame; the outer coating covers 10-100% of the area along the radial length of the support frame.

12. The covered stent according to claim 1, characterized in that, The inner coating, the outer coating, or the inner coating and the outer coating carry a drug or imaging material; the peel strength between the inner coating and the outer coating is 0.1-0.5 N / mm.

13. The covered stent according to claim 12, characterized in that, The drug includes anticoagulants and / or anti-cell proliferation drugs; the imaging material is selected from at least one of barium sulfate, niobium trioxide, titanium dioxide, zirconium oxide, iodine compounds, elemental iodine, gold, platinum, osmium, rhenium, tungsten, iridium, rhodium, and tantalum.

14. The covered stent according to claim 13, characterized in that, The anticoagulant is selected from one or more of heparin, hirudin, sodium citrate, EDTA, aspirin, warfarin, and rivaroxaban; the anti-cell proliferation drug is selected from one or more of sirolimus, tacrolimus, pimecrolimus, paclitaxel, colchicine, dexamethasone, prednisone, and hydrocortisone; the diameter of the inner and outer membrane spun fibers is 1-5 μm.

15. The covered stent according to claim 1, characterized in that, The wall thickness of the support frame is 30-300μm; the radial support force of the support frame is 90-180kpa; the peel strength between the inner and outer layers of the film-coated support is greater than the peel strength between the respective spinning fiber layers in the inner or outer film.

16. A method for preparing a covered scaffold, characterized in that, The film-coated scaffold includes an inner film, an outer film, and a support frame located between the inner and outer films, characterized in that the areas of the inner and outer films of the film-coated scaffold in the grid of the support frame are bonded to each other. The method includes the following steps: S1: Electrospin the spinning solution onto the outer wall of the adjustable diameter receiving device to form an inner coating; S2: Install the support frame on the receiving device with the inner layer film, adjust the diameter of the receiving device, and expand the inner layer film until part of the inner layer film is embedded in the grid of the support frame; S3: Electrospin the spinning solution onto the outer wall of the support skeleton to form an outer coating; S4: After the outer layer coating is completed, stop electrospinning, reduce the diameter of the receiving device and pull it out from the cavity of the coating support to obtain the coating support. In steps S1 and / or S3, the diameter of the receiving device gradually increases during the coating preparation process.

17. The method for preparing a covered scaffold according to claim 16, characterized in that, In steps S1 and / or S3, the rate at which the receiving device expands is 0.1-10 mm / h; the diameter of the inner and outer coating spun fibers is 1-5 μm.

18. The method for preparing a covered scaffold according to claim 16, characterized in that, The diameter of the inner and outer coatings spun is 1-5 μm; the depth to which the inner coating is embedded in the support skeleton grid in step S3 is 10-900 μm; the rate at which the receiving device expands in step S1 and / or S3 is 1-8 mm / h.

19. The method for preparing a covered scaffold according to claim 16, characterized in that, In step S1, after the inner layer coating is woven, the total diameter of the receiving device and the inner layer coating is less than the nominal inner diameter of the supporting skeleton; the diameter of the receiving device after the outer layer coating is prepared is 1.2-10 times the initial diameter of the receiving device in step S1; in step S3, the depth to which the inner layer coating is embedded in the grid of the supporting skeleton is 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 200μm, 230μm, 250μm, 280μm, 300μm, 350μm, 500μm, 600μm, 700μm, 800μm or 900μm.

20. The method for preparing a covered scaffold according to claim 16, characterized in that, Step S3 includes a step of spraying solvent to dissolve the inner coating spinning fibers before the outer coating is spun; the spinning solution used in steps S1 and S3 is a polymer melt in a molten state and / or a polymer solution dispersed in a solvent.

21. The method for preparing a covered scaffold according to claim 20, characterized in that, The solvent is selected from one or more of ethyl acetate, acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, dimethylacetamide, isopropanol, hexafluoroisopropanol, ethanol, and trifluoroacetic acid.

22. The method for preparing the covered scaffold according to claim 20, characterized in that, The polymer solution has a solvent-to-polymer mass ratio of 80:20-99:1; the polymer melt viscosity is 10-100 Pa·s; and the polymer melt also contains inorganic salts.

23. The method for preparing a covered scaffold according to claim 22, characterized in that, The inorganic salt is selected from one or more of the following: sodium chloride, sodium phosphate, potassium chloride, sodium chloride, magnesium chloride, aluminum chloride, sodium hydrogen phosphate, disodium hydrogen phosphate, calcium phosphate, sodium carbonate, sodium bicarbonate, calcium carbonate, calcium carbonate, ferric chloride, aluminum chloride, ferric hydroxide, ferric chloride, and ferrous gluconate.

24. The method for preparing a covered scaffold according to claim 16, characterized in that, In the textile process of steps S1 and S3, the voltage is 5-100kV, the polymer injection flow rate is 0.01-1ml / min, the distance between the receiving device and the nozzle is 2-15cm, and the rotation speed of the receiving device is 100-2000 / min.

25. A receiving device for the preparation method of the covered scaffold according to any one of claims 16-24, characterized in that, The diameter of the receiving device is adjustable, with its maximum diameter being 1.2 to 10 times the minimum diameter.

26. The receiving device for the method of preparing a coated scaffold according to claim 25, characterized in that, The surface of the receiving device is coated with a conductive coating and / or a release agent.

27. The receiving device for the method of preparing a coated scaffold according to claim 25, characterized in that, The surface of the receiving device is provided with a microporous structure, the diameter of the micropores is 10-100μm and the spacing between the micropores is 0.1-10 mm.

28. The receiving device for the method of preparing a coated scaffold according to claim 25, characterized in that, The surface of the receiving device is provided with a microporous structure, and the shape of the micropores on the surface of the receiving device is one or more combinations of strip-shaped, grid-shaped, or disordered scattered dots.

29. The receiving device for the method of preparing a coated scaffold according to claim 25, characterized in that, The receiving device is equipped with a heating component.

Citation Information

Patent Citations

  • Methods of electrospinning coating and stacking of intracavitary prostheses

    CN108136078B

  • Tubular PTFE covered stent and preparation method thereof

    CN113151980A